Moving toward a Healthy Eating Pattern: Exploring the Interrelationship of Knowledge, Attitudes, and Behavior in Young Adults - Ratna Juwita; Patronella Mateha (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: The main aim of this research is to evaluate the relationship between knowledge, attitudes and dietary behavior in young adults in the area around the Pondok Tinggi health center.. Methodology: Correlational type quantitative methods were used in this research. The sampling technique in this research used simple random sampling. The collecting technique in this research used a questionnaire on knowledge, attitudes and dietary behavior. Data analysis in this research uses correlation hypothesis testing with prerequisite tests for normality and linearity. Main Findings: The results of the analysis show that there is a significant relationship between people's knowledge and attitudes and dietary behavior. These findings indicate that better knowledge about healthy eating patterns and positive attitudes towards healthy eating patterns significantly contribute to the adoption of better eating behavior in young adults. Thus, this research provides evidence that education and increasing awareness about the importance of healthy eating patterns can be an effective strategy in improving public health. Novelty/Originality of this study: This research offers a holistic approach in evaluating the relationship between knowledge, attitudes and dietary behavior in adults aged 20-44 years around the Pondok Tinggi Community Health Center, Sungai Banyak City, Jambi province, highlighting the importance of these factors in community health promotion.